Christmas in the Lone Star State - Manning, Jason (A Texas novel of the West, 2016)
Texas Ranger Bill Sayles rode scout for Sam Houston when he was no more than fifteen. These days the lawman on the wrong side of three score years, and the glory days of the Rangers are on the wane. But Sayles still hits what he aims at and is not a man to cross. Ten days before Christmas in the harsh winter of 1876, Sayles arrives at the state prison in Huntsville to escort prisoner Jake Eddings on a furlough to his hometown, where his ten-year-old son is being laid to rest. In a desperate scheme to save his farm, Eddings took part in a stagecoach holdup in which the driver was killed. After serving two years of a fifteen-year sentence, he is already a broken man. Despite the agony of regret, he longs to see his wife and bury his beloved boy. But when Sayles gets wind that the murderous Litchfield brothers are headed in the direction of Eddings farm, the Ranger and his prisoner join forces to keep Eddings wife from harm and maybe grab a last shot at redemption.